RADIOLOGICAL BONE CHANGES IN HANSEN’S DISEASE WITH DISABILITIES/DEFORMITIES OF HANDS AND FEET: A CLINICO-RADIOLOGICAL CORRELATION - SADH, RAGHVENDRA; DUBEY, ASHISH; PAL, VISHNU (International Journal of Current Pharmaceutical Research, 2025)
Objective: To study radiological bone changes in patients of Hansen's disease with deformities of hands and feet and correlate findings with clinical parameters. Methods: Fifty leprosy patients underwent physical and radiological examination. Disability and deformities were graded as per WHO recommendations. Disability Index (DI) was calculated using. Bone changes were categorized as specific, non-specific, and osteoporotic. Data were correlated with clinical variables. Results: Radiological bone changes were present in 88% of cases. Specific changes were seen in 34% (e. g., subarticular erosion), non-specific in 82% (e. g., terminal phalanx absorption), and osteoporotic changes in 34% (mainly minimal osteoporosis). Significant correlation was found between non-specific and osteoporotic changes with increasing duration of disease, deformity, and DI. Conclusion: Radiological bone changes are prevalent in Hansen’s disease, especially in patients with longer disease duration and higher DI. Specific changes showed no significant correlation with clinical variables, while non-specific and osteoporotic changes correlated with disease progression and disability.